AKTIVITAS ANTIBAKTERI EKSTRAK BIJI JERUK SIAM (Citrus reticulata) PADA BAKTERI Escherichia coli - Mohammad Arfi Setiawan; Mita Dewi Retnoningrum; Febriyandhi Yahya; Resa Ragil Andika; Dyan Hatining Ayu Sudarni (Balai Bioteknologi, Badan Pengkajian dan Penerapan Teknologi (BPPT), 2020)
Antibacterial Activity of Citrus seed (Citrus reticulata) Extract on Escherichia coli Indonesian agriculture provides a resource of medicinal plants whose potential needs to be explored in order to benefit society. One of them is the use of Siam orange seeds (Citrus reticulata) which has the potential for the production of antibacterial compounds. This study aims to test the antibacterial activity of the ethanol and n-hexane extract of orange seeds. The extract was obtained through maceration techniques using ethanol and n-hexane as solvents. The antibacterial activity test of orange seeds against Escherichia coli used the paper disc diffusion method with nutrient agar (NA) media. The concentration of orange seed extract for the determination of MIC (Minimum Inhibitory Concentration) was 0.5, 2, 8, 10, 20 mg mL-1. The results showed that the ethanol and n-hexane extract of orange seeds had antibacterial activity against E. coli. However, the ethanol extract had a higher antibacterial effect than the n-hexane orange seed extract. From the results of this study, it is hoped that the waste of orange seeds will provide beneficial contribution for pharmaceutical development. Pertanian Indonesia memiliki sumber tanaman obat yang perlu digali potensinya agar bermanfaat bagi masyarakat. Salah satunya pemanfaatan biji jeruk siam (Citrus reticulata) yang berpotensi menghasilkan senyawa antibakteri. Penelitian ini bertujuan untuk menguji aktivitas antibakteri ekstrak etanol dan n-heksana biji jeruk. Ekstrak diperoleh melalui teknik maserasi menggunakan pelarut etanol dan n-heksana. Uji aktivitas antibakteri biji jeruk terhadap Escherichia coli menggunakan metode difusi paper disc dengan media nutrient agar (NA). Konsentrasi ekstrak biji jeruk untuk penentuan MIC (Minimum Inhibitory Concentration) adalah 0,5, 2, 8, 10, 20 mg mL-1. Hasil penelitian menunjukkan bahwa ekstrak etanol dan n-heksana biji jeruk memiliki aktivitas antibakteri terhadap E. coli. Namun, ekstrak etanol memiliki efek antibakteri yang lebih tinggi dibandingkan ekstrak biji jeruk n-heksana. Dari hasil penelitian ini, limbah biji jeruk diharapkan dapat memberikan kontribusi bermanfaat bagi pengembangan farmasi.